Effect of Surface Application of Sanhua Ointment on Cartilage and Synovial Tissue in MIA-induced Osteoarthritis - Jin, Jiming; Qi, Haodong; Guo, Hao; Hao, Yangquan; Yuwen, Xing; Lu, Chao (Journal of Contemporary Medical Practice, 2025)
Objective: To investigate the effects of topical application of Sanhua Ointment on cartilage and synovial tissues in a mouse model of osteoarthritis. Methods: Forty-five mice were randomly divided into three groups: control, model, and treatment groups, with 15 mice in each group. The model and treatment groups were induced to develop osteoarthritis by intra-articular injection of sodium Monoiodoacetate (MIA). On the fourth day after modeling, the treatment group was administered Sanhua Ointment on the surface of the knee joint. The control and model groups were treated with Vaseline, with medication administered continuously for 12 days. The diameter of the mouse knee joint was measured every 4 days. After the 16th day, samples were collected and subjected to Micro-CT scanning, hematoxylin-eosin staining, safranin O-fast green staining, Masson’s staining, and immunohistochemical staining. Results: Compared with the control group, the knee joint diameter of mice in the model group was significantly higher at days 4, 8, and 12 after modeling (P<0.05); on day 12, the knee joint diameter of mice in the treatment group was significantly lower than that in the model group (P<0.05). Micro-CT results showed that the BV/TV and Tb.Th in the model group were significantly lower than those in the control group (P<0.01), and Tb.Sp was significantly higher than that in the control group (P<0.01). In the treatment group, BV/TV and Tb.Th were significantly higher than in the model group (P<0.01), and Tb.Sp was significantly lower than in the model group (P<0.001). Safranin O-fast green staining indicated joint cartilage damage in the model group, with thinning of the cartilage layer and a rough surface, while the cartilage structure in the treatment group was more complete compared to the model group. Hematoxylin-eosin staining revealed severe synovial hyperplasia in the model group, with inflammatory cell infiltration into the synovium, while the treatment group showed a significant reduction in synovial hyperplasia and inflammatory infiltration compared to the model group. Masson’s staining showed that the proportion of fibrotic areas in the model group was significantly higher than that in the control group (P<0.01), and the treatment group was significantly lower than the model group (P<0.01). Immunohistochemical results indicated that the expression of Collagen II in the cartilage layer of the model group was significantly lower than that in the control group (P<0.001), and the expression of MMP13 was significantly higher than that in the control group (P<0.001); compared with the model group, the expression of Collagen II in the treatment group was significantly increased (P<0.001), and the expression of MMP13 was significantly decreased (P<0.01). The Western Blot results indicated that the expression of Collagen II in the model group was significantly lower than that in the control group (P<0.001), while the expression of MMP13 was significantly higher than that in the control group (P<0.001). Compared with the model group, the expression of Collagen II in the treatment group was significantly increased (P<0.001), and the expression of MMP13 was significantly decreased (P<0.01). Conclusion: Sanhua Ointment may delay the pathological progression of OA by inhibiting cartilage degradation and synovial inflammation.